2009
DOI: 10.1097/bot.0b013e3181a2e2b6
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy After Severe Open Fractures: A Prospective Randomized Study

Abstract: Control patients developed 2 acute infections (8%) and 5 delayed infections (20%), for a total of 7 deep infections (28%), whereas NPWT patients developed 0 acute infections, 2 delayed infections (5.4%), for a total of 2 deep infections (5.4%). There is a significant difference between the groups for total infections (P = 0.024). The relative risk ratio is 0.199 (95% confidence interval: 0.045-0.874), suggesting that patients treated with NPWT were only one-fifth as likely to have an infection compared with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
184
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 293 publications
(199 citation statements)
references
References 40 publications
7
184
0
8
Order By: Relevance
“…The infection rates were equivalent at 14% for gauze dressings and 15% for negative pressure wound therapy in their study [45]. The patients in the two studies [7,49] with decreased and the one [45] with equivalent infection rates and negative pressure wound therapy dressings all had wound closure within 7 days. Liu et al, in a retrospective study [35], reported increased infection rates with negative pressure wound therapy.…”
Section: Negative Pressure Wound Therapy and Infection Reduction In Gmentioning
confidence: 94%
See 4 more Smart Citations
“…The infection rates were equivalent at 14% for gauze dressings and 15% for negative pressure wound therapy in their study [45]. The patients in the two studies [7,49] with decreased and the one [45] with equivalent infection rates and negative pressure wound therapy dressings all had wound closure within 7 days. Liu et al, in a retrospective study [35], reported increased infection rates with negative pressure wound therapy.…”
Section: Negative Pressure Wound Therapy and Infection Reduction In Gmentioning
confidence: 94%
“…One hundred were excluded based on their titles most commonly because of inclusion of chronic or diabetic wounds. We reviewed the abstracts of the seven remaining studies and only one [49] included Grade IIIB tibia fractures, negative pressure wound therapy, and any of our outcome questions. A second search protocol was used with the databases of MEDLINE 1 , Embase, and Google Scholar (Fig.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 3 more Smart Citations